Land Use Change and Its Impacts on Surface Runoff in Rural Areas of the Upper Citarum Watershed (Case Study: Cirasea Sub-watershed) - Zahrul Atharinafi; Nurrohman Wijaya (Journal of Regional and City Planning, 2021)
Land-use change in upstream regions is a recognized driver of the increase in surface runoff, resulting in increasing flood intensity and occurrence. The rapid urbanization of outlying districts surrounding large metropolitan areas is a known driver of land-use change. Therefore, we study land-use change patterns within the Cirasea Sub-watershed within the last 20 years and changes in the runoff coefficient within the same time frame. This paper examines how land-use change patterns on the outskirts of the Bandung Metropolitan Area influence runoff. Spatial analysis and surface runoff calculation using the curve number method were applied. The study found significant changes in land use, particularly in the watershed's southern reaches, whereby forest and shrub land gave way to agriculture in a water recharge zone, resulting in an increased runoff coefficient upstream. Urbanization within the Cirasea Sub-watershed did not encroach into areas identified as recharge zones and had a minimal direct impact on increased runoff. Aggregate runoff coefficient (curve number) in the Cirasea Sub-watershed increased from 70.98 in 1999 to 72.04 in 2018. For a design 24-hour period rainfall of 120 mm, runoff increased from 48.49 mm (1999) to 51.8 mm (2018). We conclude that the changes above in land use have increased runoff in the Cirasea Sub-watershed. Furthermore, land-use policies laid down by the RTRW Bandung Regency for 2016-2036 provide provisions to reforest previously deforested areas, with deforested areas being zoned as protected forest. Therefore, we propose promoting agroforestry as part of land use policy in order to restore runoff to its 1999 level under existing land use planning policy.Abstrak. Perubahan guna lahan pada wilayah hulu diketahui sebagai salah satu penyebab peningkatan limpasan air permukaan, meningkatkan intensitas dan frekeuensi banjir. Urbanisasi pesat pada wilayah pinggiran kawasan metropolitan diketahui sebagai faktor pendorong terjadinya perubahan guna lahan. Berdasarkan kondisi tersebut, kami melakukan studi terhadap pola perubahan guna lahan pada Sub-DAS Cirasea, pada 20 tahun terakhir, serta perubahan limpasan air permukaan pada rentang waktu yang sama. Paper ini meneliti bagaimana perubahan guna lahan pada wilayah pinggiran Metropolitan Bandung Raya mempengaruhi limpasan air permukaan. Analisis spasial dan perhitungan limpasan air permukaan dilakukan, menggunakan metode bilangan kurva. Berdasarkan hasil studi, diketahui telah terjadi perubahan guna lahan yang signifikan pada wilayah hulu DAS. Hutan dan semak belukar berubah menjadi kawasan pertanian, pada wilayah resapan air tanah, sehingga terjadi peningkatan limpasan air permukaan di wilayah hulu. Urbanisasi pada wilayah Sub-DAS Cirasea diketahui tidak menjalar hingga wilayah resapan air tanah dan memiliki dampak minim terhadap kenaikan limpasan air permukaan. Angka koefisien limpasan air permukaan (bilangan kurva) di DAS Cirasea meningkat dari 70.98 (1999), menjadi 72.04 (2018). Pada curah hujan (asumsi) 24 jam sebesar 120mm, limpasan air permukaan meningkat dari 48.49mm (1999), menjadi 51.8mm (2018). Berdasarkan hasil tersebut, kami simpulkan bahwa perubahan guna lahan telah mengakibatkan peningkatan limpasan air permukaan di DAS Cirasea.  Kata kunci.Perubahan tata guna lahan, potensi aliran permukaan, DAS citarum hulu, pencegahan banjir.